Sea bass and bream in floating cages in Turkey - Sahin M. (Aspects économiques de la production aquacole, 1995)
This presentation has been prepared on experimental data on the basis of our company's background of 8 years in the sector, as well as our regular contacts with the other fish farms because of marketing and distribution of juveniles from our hatchery, and giving the ecological conditions, meteorological conditions of the locations in Turkey, production systems, capacity of the functioning hatcheries and fish farms, employment of the sector, zootechnical standards, marketing conditions, investments, economic aspects and the economic results of small scale sea bass and sea bream in floating cages in Turkey.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)